2010
DOI: 10.1007/s00384-010-0980-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 5-lipoxygenase in sporadic colonic adenomas and a possible new aspect of colon carcinogenesis

Abstract: PurposeWe aimed to study the intracellular expression of 5-lipoxygenase (5-LOX), the primary competitor with cyclooxygenase-2 in arachidonic acid metabolism, as inflammatory enzymes may be involved in blocking apoptosis and promoting cancer growth by changing arachidonic acid metabolism within cells. Our purpose was to investigate the possible connection between 5-LOX expression and colon carcinogenesis by characterizing 5-LOX expression in histologically different colonic adenomas, determining the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…However, the tissue concentrations of 13S-HODE declined across this progressive sequence. In a separate study a strong correlation between ALOX5 expression and increased polyp size as well as higher tumor grade suggested a role for this enzyme in early stages of colon cancer [120]. These data are consistent with the overexpression of ALOX5 in colon polyps and carcinoma tissue described in another study [121].…”
Section: Biological Function Of Mammalian Lox Isoformssupporting
confidence: 85%
“…However, the tissue concentrations of 13S-HODE declined across this progressive sequence. In a separate study a strong correlation between ALOX5 expression and increased polyp size as well as higher tumor grade suggested a role for this enzyme in early stages of colon cancer [120]. These data are consistent with the overexpression of ALOX5 in colon polyps and carcinoma tissue described in another study [121].…”
Section: Biological Function Of Mammalian Lox Isoformssupporting
confidence: 85%
“…The DHET metabolites were not significantly changed, but 12-HETEs did decrease. Products from 5- and 12-lipoxygenases have been associated with enhanced carcinogenesis in multiple epithelia (26, 27, 32). Colon 12-S- and 12-R-HETEs were substantially reduced by ω-3 fatty acid supplementation (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…5-LOX may directly control tumour cell function or indirectly affect the tumour microenvironment. Increased 5-LOX activity has been demonstrated to play a role in the early stages of colon cancer (53) and in carcinogenesis in human oral cavity tissues (54). It was also reported that 5-LOX expression may be involved in the development of BCR-ABL-induced chronic myeloid leukaemia (55).…”
Section: Loxs and Their Inhibitors In Cancer Treatmentmentioning
confidence: 97%